Cooperative monitoring program for a catch-and-release recreational fishery in the Alphonse Island group, Seychelles: From data deficiencies to the foundation for science and management. (1st September 2021) - Griffin, Lucas P.; Adam, Pierre-André; Fordham, Gail; Curd, George; McGarigal, Caitlin; Narty, Christopher; Nogués, Josep; Rose-Innes, Keith; Merwe, Devan Vd; Danylchuk, Sascha Clark; Cooke, Steven J.; Danylchuk, Andy J.
Abstract: Recreational fishing is a growing sector of tourism, and in theory, can be done in a sustainable manner such as through catch-and-release where fish are released rather than harvested. In some cases, stakeholders have taken the initiative to develop conservation strategies and management guidelines, as well as establishing monitoring programs of the resources they use. In this work, we provide a case study of a cooperative monitoring program in the Alphonse Group, Republic of the Seychelles, Africa, between a fishing company (Alphonse Fishing Company) and a local non-governmental organization (Island Conservation Society). These efforts have resulted in a code of conduct for the catch-and-release of target species, as well as long-term spatially explicit monitoring of catches, including fish size and catch location for five popular species through catch logs. During three seasons, the five key fish species monitored were giant trevally ( Caranx ignobilis, n = 684), moustache triggerfish ( Balistoides viridescens, n = 141), Indo-Pacific permit ( Trachinotus blochii, n = 99), milkfish ( Chanos chanos, n = 55), and yellowmargin triggerfish ( Pseudobalistes flavimarginatus, n = 46). We found monthly catch variability across all species and that catches across seasons increased for C. ignobilis (203.8%), T. blochii (45.5%), and B. viridescens (25%), and decreased for C. chanos (-65.6%) and P. flavimarginatus (-10%) . Although there are considerations with implementing and maintaining such initiatives, we reviewed the benefits, including how these efforts can serve as the foundation for more thorough scientific research, co-production, and evidence-based management for the most sought-after species, C. ignobilis . We highlight how these cooperative initiatives may lead to formal co-management structures in recreational fishing, and also help to build capacity in government agencies for advancing economic prosperity while establishing sound long-term management and conservation strategies. Highlights: Remote tourism-based catch-and-release recreational angling ventures are emerging. Baseline fisheries data is often lacking but needed for sustainable use. Catch log data provided spatially explicit maps of high-pressured fishing areas. Monitoring by stakeholders provides foundation for evidence-based management. Data collection may be inhibited due to competing demands with monitoring programs.